ANALISIS KESEJAHTERAAN PENYANDANG DISABILITAS TUNANETRA DI YAYASAN PENDIDIKAN TUNANETRA SUMATERA (YAPENTRA) TANJUNG MORAWA - Adilah, Asri; Berlianti, Berlianti (Triwikrama: Jurnal Ilmu Sosial, 2025)
Abstract Welfare is a condition where a human feels that his life is prosperous. The sense of well-being itself arises from freedom from fear and freedom from pressure. One of the welfare indicators is education and all citizens have the same right to quality education and this applies to Indonesian citizens with physical, emotional, mental, intellectual and social disabilities. Physical limitations such as blind people are not an obstacle to getting an education. The research was conducted at the Sumatra Blind Education Foundation (YAPENTRA) Tanjung Morawa. The aim of this research is to determine the welfare of people with disabilities at Yapentra Tanjung Morawa. The education provided by the Sumatran Blind Education Foundation (YAPENTRA) Tanjung Morawa is formal education and non-formal education. Formal education is education like regular children in general who study regular children's subjects. Non-formal education is a training and skills education program to form the independence of blind students at Yapentra Tanjung Morawa. The key informant is the Principal of the Yapentra Tanjung Morawa School. The main informants are the blind students of Yapentra Tanjung Morawa, as well as additional informants, namely two teaching staff and one parent of a blind person. Data collection techniques using observation, in-depth interviews, and literature study. The data obtained in the field was then analyzed by researchers who explained using qualitative methods. The results of the research show that the welfare of blind students at Yapentra Tanjung Morawa has been met in several indicators such as income, expenses, education, health and housing. Keywords: Welfare, education, blind people with disabilities. Abstrak Kesejahteraan adalah suatu kondisi dimana seseorang manusia merasa hidupnya sejahtera. Rasa sejahtera itu sendiri timbul akibat kebebasan dari ketakutan dan bebas dari tekanan-tekanan. Indikator kesejahteraan salah satunya ialah pendidikan dan semua warga memiliki hak yang sama atas pendidikan yang bermutu dan berlaku untuk WNI dengan cacat fisik, emosional, mental, intelektual, dan sosial. Keterbatasan fisik seperti penyandang disabilitas tunanetra tidak menjadi halangan untuk mendapatkan pendidikan. Penelitian dilakukan di Yayasan Pendidikan Tunanetra Sumatera (YAPENTRA) Tanjung Morawa. Tujuan penelitian ini ialah untuk mengetahui kesejahteraan penyandang disabilitas di Yapentra Tanjung Morawa. Pendidikan yang diberikan oleh Yayasan Pendidikan Tunanetra Sumatera (YAPENTRA) Tanjung Morawa ialah pendidikan formal dan pendidikan nonformal. Pendidikan formal ialah pendidikan seperti anak reguler pada umumnya yang mempelajari mata pelajaran anak regular. Pendidikan nonformal ialah program pendidikan pelatihan dan keterampilan untuk membentuk kemandirian siswa-siswi tunanetra di Yapentra Tanjung Morawa. Informan Kunci yaitu Kepala Sekolah Yapentra Tanjung Morawa. Informan Utama yaitu siswa-siswi tunanetra Yapentra Tanjung Morawa, serta informan tambahan yaitu dua staf pengajar dan satu orangtua dari penyandang disabilitas tunanetra. Teknik pengumpulan data dengan observasi, wawancara mendalam, dan studi pustaka. Data yang didapat di lapangan kemudian di analisis oleh peneliti yang dijelaskan menggunakan metode kualitatif. Hasil penelitian menunjukkan sudah terpenuhinya kesejahteraan siswa-siswi tunanetra yang berada di Yapentra Tanjung Morawa di beberapa indikator seperti pendapatan, pengeluaran, pendidikan, kesehatan, dan juga perumahan. Kata kunci : Kesejahteraan, pendidikan, penyandang disabilitas tunanetra.